ANALYSIS OF AI USAGE IN BIOLOGY EDUCATION IN THE 5.0 ERA: A QUALITATIVE STUDY ON STUDENTS' PERSPECTIVES - Yolanda, Dwi; Desviana Siregar , Anggi; Rizkiyanti Zebua, Dinyah (Universitas Lancang Kuning, 2024)
The Society 5.0 era places technology as a key element in improving the quality of life, including in the field of education. In this context, artificial intelligence (AI) has become one of the increasingly used technologies by students to support the learning process. This study aims to analyze the use of AI, particularly ChatGPT, in the learning process of fifth-semester Biology Education students at IAIN Kerinci. This research employs a descriptive qualitative approach with data collection techniques through interviews conducted online using Google Forms. The results of the study show that the majority of students have used ChatGPT in their academic activities and have experienced significant benefits in terms of accelerating understanding of materials, completing assignments, and reducing workload. However, this research also identifies several challenges in using AI, such as the inaccuracy of answers and the lack of adequate reference sources. Nevertheless, students remain critical and do not fully rely on AI, instead, they use it as a tool that complements traditional learning methods. With further development, AI has great potential to enhance learning effectiveness in the academic environment.